Quercetin synergistically induces sensitivity to 5-fluorouracil through p53 modulation in colorectal cancer cells - Xavier, Cristina P. R. (2011)
Colorectal tumors (CRC) with microsatellite instability (MSI) show resistance to chemotherapy with 5-fluorouracil (5-FU), the most widely used pharmacological drug for CRC treatment. The aims of this study were to identify compounds that increase sensitivity of MSI CRC cells to 5-FU and characterize their dependence on the p53 status of the cells. Two MSI human CRC derived cell lines were used: CO115 wildtype for p53 and HCT15 that harbors a p53 mutation. The sensitivity of these cells to 5-FU was evaluated by TUNEL assay and the effects on apoptosis induction of co-incubation of the flavonoids, quercetin (Q) or luteolin (L), with 5-FU were characterized. The mechanisms of apoptosis induction were assessed by western blot and p53 mediated effects confirmed by small interference RNA (siRNA) in CO115 and in HCT116 wt and p53 knockout cells. Our results demonstrate that CO115 is more sensitive to 5-FU than the p53 mutated HCT15. Additive effects on apoptosis were shown for L (in both cell lines) and Q (in HCT15). In CO115 Q synergistically induced apoptosis with 5-FU. Apoptosis induction was caspase dependent in CO115 cells but not in HCT15 cells. Both flavonoids increased p53 expression in both cell lines, an effect particularly remarkable for Q. The synergistic effect of Q and 5-FU in CO115 involved the activation of the mitochondrial pathway with an increase in the expression of cleaved caspase 9 and 3 and PARP, as well as a decrease in Bcl-2 expression. Importantly, knockdown of p53 by siRNA in CO115 cells and p53 knockout in HCT116 cells totally abrogated apoptosis induction, demonstrating the dependence on p53 modulation of apoptosis induction by Q. This study suggests the potential applicability of these phytochemicals for enhancement 5-FU efficiency in CRC therapy, especially Q in p53 wild-type tumors.